Comparative evolutionary pharmacogenetics of CYP2D6 in Ngawbe and EmberaAmerindians of Panama and Colombia:role of selection versus drift in world populations (2022)
eng: The development of CYP2D6 has been attributed to the need of earth-dwelling animals to detoxify toxic xenobiotics (phytoalexins) present in plants. This hypothesis has been extrapolated to humans, but is yet unconfirmed. Therefore, we studied two Amerindian populations as the best available model to test the effect of selection through diet on human CYP2D6 evolution. The frequency of sparteine poor metabolizers in Ngawbe was 4.4% (n = 344), while the frequency in Embera was 2.2% (n = 153). Among Ngawbe and Embera, CYP2D6*4 (allelic frequencies for each tribe, respectively: 0.171; 0.14), CYP2D6*6 (0.005; 0.011) and CYP2D6*10 (0.175; 0.069) were detected, while CYP2D6*3, CYP2D6*5, CYP2D6*9 and CYP2D6*16 were absent. All poor metabolizers possessed either CYP2D6*4 or CYP2D6*6 and there were no disagreements between genotypic and phenotypic data. The total frequency of mutant alleles showed no difference among Amerindians or when compared to Caucasians. It was higher than in Chinese, since the frequency of CYP2D6*4 was higher in Amerindians. XbaI restriction fragment length polymorphisms haplotypes were very homogeneous in Amerindians, because the only fragment that hybridized with the CYP2D6 cDNA probe was the 29 kb (not 42/44 kb or 11.5/13 kb). This indicated no gene cluster recombinations that generate insertions or deletions. We propose that in earlier hominids and humans, CYP2D6 had increasingly become a vestigial characteristic unconstrained by dietary stressors, as a result of cultural survival strategies. Human CYP2D6 evolution was preferentially affected by random genetic drift, and not by adaptive or purifying selection.